2007
DOI: 10.1083/jcb.200612043
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of protrusion, adhesion dynamics, and polarity by myosins IIA and IIB in migrating cells

Abstract: We have used isoform-specific RNA interference knockdowns to investigate the roles of myosin IIA (MIIA) and MIIB in the component processes that drive cell migration. Both isoforms reside outside of protrusions and act at a distance to regulate cell protrusion, signaling, and maturation of nascent adhesions. MIIA also controls the dynamics and size of adhesions in central regions of the cell and contributes to retraction and adhesion disassembly at the rear. In contrast, MIIB establishes front–back polarity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
422
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(465 citation statements)
references
References 42 publications
41
422
2
Order By: Relevance
“…This view is supported by the recent report showing that the expressed MHC-IIB, in which the PKC phosphorylation sites were converted to Asp residues, was able to localize at the stress fibers, but this mutation attenuated the localization of the mutant MHC-IIB to the cell cortex (Rosenberg and Ravid, 2006). Moreover, it was recently reported that myosin II isoforms (IIA and IIB) differentially contributes to the cell motility (Even-Ram et al, 2007;Vicente-Manzanares et al, 2007), suggesting that myosin isoforms are regulated by distinct mechanisms in motile cells. Supporting this notion, biochemical studies revealed that phosphate incorporation of MHC-IIB by PKC is much faster than that of myosin IIA and, in contrast, that filament assembly of myosin IIA is regulated by its binding protein (Mts1) but not that of myosin IIB (Murakami et al, 1998(Murakami et al, , 2000Dulyaninova et al, 2005).…”
Section: Discussionsupporting
confidence: 71%
“…This view is supported by the recent report showing that the expressed MHC-IIB, in which the PKC phosphorylation sites were converted to Asp residues, was able to localize at the stress fibers, but this mutation attenuated the localization of the mutant MHC-IIB to the cell cortex (Rosenberg and Ravid, 2006). Moreover, it was recently reported that myosin II isoforms (IIA and IIB) differentially contributes to the cell motility (Even-Ram et al, 2007;Vicente-Manzanares et al, 2007), suggesting that myosin isoforms are regulated by distinct mechanisms in motile cells. Supporting this notion, biochemical studies revealed that phosphate incorporation of MHC-IIB by PKC is much faster than that of myosin IIA and, in contrast, that filament assembly of myosin IIA is regulated by its binding protein (Mts1) but not that of myosin IIB (Murakami et al, 1998(Murakami et al, , 2000Dulyaninova et al, 2005).…”
Section: Discussionsupporting
confidence: 71%
“…Myosins IIA and IIB both contribute to the process of cell migration (Kolega, 2006;Ma et al, 2006;Vincente-Manzanares et al, 2007), and in breast carcinoma cells, they have distinct roles (Betapudi et al, 2006). The enzymatic activity of each of the myosin II isoforms is controlled by phosphorylation of the regulatory light chain (RLC), a process largely catalyzed by two regulatory kinases-myosin light chain kinase and rho kinase (Tan et al, 1992;Amano et al, 1996).…”
Section: Myosin II Isoform Expression In Gliomasmentioning
confidence: 99%
“…Nonmuscle myosin (NM) II, one of the major cytoskeletal motor proteins, plays an important role in cell migration (Svitkina et al, 1997;Ma et al, 2004;Even-Ram et al, 2007;Vicente-Manzanares et al, 2007), cell-cell adhesion Shewan et al, 2005;Giannone et al, 2007), and cell division (De Lozanne and Spudich, 1987;Takeda et al, 2003;Bao et al, 2005). The molecular structure of NM II is a hexamer consisting of a pair of myosin heavy chains (200 kDa) and two pairs of light chains (20 and 17 kDa).…”
Section: Introductionmentioning
confidence: 99%
“…The defect may be accompanied by an obstructed aqueduct of Sylvius, the narrow channel connecting the third and fourth brain ventricles (noncommunicating hydrocephalus), or by a normal aqueduct (communicating hydrocephalus). The pathogenesis of most cases of communicating hydrocephalus is largely unknown (for reviews, see Perez-Figares et al, 2001;Crews et al, 2004).Nonmuscle myosin (NM) II, one of the major cytoskeletal motor proteins, plays an important role in cell migration (Svitkina et al, 1997;Ma et al, 2004;Even-Ram et al, 2007;Vicente-Manzanares et al, 2007), cell-cell adhesion Shewan et al, 2005;Giannone et al, 2007), and cell division (De Lozanne and Spudich, 1987;Takeda et al, 2003;Bao et al, 2005). The molecular structure of NM II is a hexamer consisting of a pair of myosin heavy chains (200 kDa) and two pairs of light chains (20 and 17 kDa).…”
mentioning
confidence: 99%